Analisis Pengaruh Pembiayaan Mudharabah, Musyarakah Dan Murabahah Terhadap Return on Asset (ROA) Bank Umum Syariah di Indonesia - Suprianto, Joko; Kurahman, Taufik; Mukhlis, Yazid (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the effect of Mudharabah, Musyarakah, and Murabahah financing on Return on Assets (ROA) of Islamic Commercial Banks in Indonesia during the period 2019 to 2023. These three types of financing are the main instruments in Islamic banking operations and have different characteristics and risk profiles that influence the bank's profitability. This research adopts a quantitative approach using secondary data obtained from the financial reports of Islamic Commercial Banks registered with the Financial Services Authority (OJK). Data analysis is conducted using multiple linear regression to examine both the simultaneous and partial effects of the three financing types on ROA. The results show that, simultaneously, Mudharabah, Musyarakah, and Murabahah financing have a significant effect on ROA. Partially, Murabahah financing has a positive and significant effect, while Mudharabah and Musyarakah show varying influences. These findings offer important implications for Islamic bank management in optimizing their financing portfolios to enhance financial performance, particularly in improving profitability ratios.